2022
DOI: 10.3390/ani12243541
|View full text |Cite
|
Sign up to set email alerts
|

Protective Application of Morus and Its Extracts in Animal Production

Abstract: Different components of the mulberry tree (fruits, leaves, twigs, and roots) are rich in active compounds, and have been reported to possess potent beneficial properties, including antioxidative, anti-inflammatory, antimicrobial, anticancer, anti-allergenic, antihypertensive, and neuroprotective. The mulberry and its extracts can effectively improve the growth performance and fitness of animals. They not only possess the properties of being safe and purely natural, but also they are not prone to drug resistanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 120 publications
(147 reference statements)
0
4
0
Order By: Relevance
“…Mulberry leaf powder supplementation improved the color (redness), tenderness, and water retention of the longissimus lumborum muscle in Hu lambs [ 67 ]. The mulberry and its extracts are known to improve immune function and suppress enteric methane production in ruminants [ 68 ], and it is speculated they could alter the rumen and gut microbiome which can impact on muscle growth and lipid profiles. Indeed, partial replacement of Chinese wild rye with mulberry leaves in the diet of sheep decreased saturated FA content and increased unsaturated FA content in longissimus dorsi muscle [ 69 ].…”
Section: Association Between Beef Meat Quality and Methane Emissionmentioning
confidence: 99%
“…Mulberry leaf powder supplementation improved the color (redness), tenderness, and water retention of the longissimus lumborum muscle in Hu lambs [ 67 ]. The mulberry and its extracts are known to improve immune function and suppress enteric methane production in ruminants [ 68 ], and it is speculated they could alter the rumen and gut microbiome which can impact on muscle growth and lipid profiles. Indeed, partial replacement of Chinese wild rye with mulberry leaves in the diet of sheep decreased saturated FA content and increased unsaturated FA content in longissimus dorsi muscle [ 69 ].…”
Section: Association Between Beef Meat Quality and Methane Emissionmentioning
confidence: 99%
“…However, the utilization of mulberry leaves is less, and most of the mulberry leaves produced every year are discarded as waste, and a small part of mulberry leaf resources are mainly used for breeding, food processing and medicine etc. [ 11 , 12 ]. As a kind of Chinese herbal medicine, mulberry leaves contain bioactive components such as flavonoids, polysaccharides, and alkaloids [ 13 ], which have the functions of lowering blood sugar, blood fat, and protecting the liver [ 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…Mulberry (Morus alba L.) is widely planted worldwide and has advantages such as a well-developed root system, drought resistance, salinity tolerance and strong vitality. 4 It has been reported that mulberry leaves are rich in many natural active substances, such as polysaccharides, flavonoids and alkaloids, and have high nutritional and medicinal value. 5 However, the single mode of mulberry planting and silkworm raising leads to low utilization of sericulture resources.…”
Section: Introductionmentioning
confidence: 99%
“…5 However, the single mode of mulberry planting and silkworm raising leads to low utilization of sericulture resources. 4,6 By contrast, the market demand for livestock and poultry products continues to expand, whereas the primary source of feedstock for the livestock industry in China is grain crops. 1 Traditional sources of raw materials are no longer sufficient to support the enormous demand for livestock development, and the innovative development of new feed sources has been the general trend.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation